Optimizing Packing Operations with an Integrated Barcode Warehouse System: Mengoptimalkan Operasi Pengemasan dengan Sistem Gudang Barcode Terpadu - Cahyono, Priyo Imam; Hindarto, Hindarto (Indonesian Journal of Law and Economics Review, 2024)
General background: Business competition in the globalization era demands companies enhance operational efficiency, particularly in warehouse management. Specific background: Packing operations significantly influence the supply chain’s effectiveness, affecting goods availability, delivery speed, and customer satisfaction. However, challenges like manual errors, slow item identification, and lack of integration between warehouse management systems and modern technologies persist. Knowledge gap: Despite the increasing use of warehouse management systems, the potential of integrating barcode technology to optimize packing operations has not been fully explored. Aims: This study aims to examine the optimization potential of packing operations using an integrated barcode-based warehouse management system. Results: By employing the SDLC waterfall model for application development, the integrated system showed improvements in item identification efficiency, minimized packing errors, and enhanced inventory accuracy. Novelty: The proposed approach demonstrates how barcode technology can streamline warehouse management processes, which is not thoroughly documented in existing literature. Implications: These findings provide insights for companies to develop effective strategies and technologies to improve warehouse operations, ensuring a stronger position in the competitive market. Highlights: Barcode integration improves packing speed and accuracy. The system reduces manual errors in warehouse operations. Enhances inventory management for better supply chain performance. Keywords: Packing Optimization, Warehouse Management, Barcode Integration, Efficiency, Inventory Accuracy